Fully Λ-doublet resolved state-to-state differential cross-sections for the inelastic scattering of NO(X) with Ar. - Eyles, C; Brouard, M; Chadwick, H; Hornung, B; Nichols, B; Yang, C; Kłos, J; Aoiz, F; Gijsbertsen, A; Wiskerke, A; Stolte, S (2012)
Fully Λ-doublet resolved state-to-state differential cross-sections (DCSs) for the collisions of the open-shell NO(X, (2)Π(1/2), ν = 0, j = 0.5) molecule with Ar at a collision energy of 530 cm(-1) are presented. Initial state selection of NO(X, (2)Π(1/2), j = 0.5, f) was performed using a hexapole so that the (low field seeking) parity of ε = -1, corresponding to the f component of the Λ-doublet, could be selected uniquely. Although the Λ-doublet levels lie very close in energy to one another and differ only in their relative parities, they exhibit strikingly different DCSs. Both spin-orbit conserving and spin-orbit changing collisions have been studied, and the previously unobserved structures in the fully quantum state-to-state resolved DCSs are shown to depend sensitively on the change in parity of the wavefunction of the NO molecule on collision. In all cases, the experimental data are shown to be in excellent agreement with rigorous quantum mechanical scattering calculations.